ACADEMIC INTEGRITY PHENOMENON IN THE CONTEXT OF SCIENTIFIC APPROACHES SYNERGY - Batechko Nina; Mykhaylicheko Mykola (Borys Grinchenko Kyiv Metropolitan University, 2019)
The article highlights the phenomen of academic integrity in the context of the synergy of scientific approaches: systemic and synergetic. It has been indicated that such an interpretation can serve as the theoretical and methodological basis of the phenomenon under study. The definitional analysis of the problem of ensuring academic integrity, which is present in the scientific circulation both in Ukraine and abroad, has been carried out. It has been proved that academic integrity, on the one hand, is a complex interdisciplinary category that combines ethical standards and rules of human behaviour in the educational and scientific environment and the mechanisms and tools by which the latter are put into practice. In the context of a systematic approach, the levels of implementation of the basic principles of academic integrity have been presented: international, national, state, higher education institution and personality levels. Understanding of ensuring academic integrity at various levels will allow taking into account the features of the phenomenon under study both at the level of society life and at the level of an individual. In the context of the synergetic approach, academic integrity has been considered as a nonlinear dynamic system capable of self-organization. The best foreign and domestic practices of ensuring academic integrity at different levels have been provided. The developed methodology can contribute to the creation of evolutionary models for the development of the system of academic integrity in Ukraine and the effective management of this process.